How do contralateral calcaneal quantitative ultrasound measurements in male professional football (soccer) players reflect the effects of high-impact physical activity on bone? - Tarakçi, D.; Oral, A. (The Journal of Sports Medicine and Physical Fitness, 2009)
Aim. The aim of this study was to examine how the influence of football (soccer) on bone tissue was reflected by the acoustic parameters of bone as measured by calcaneal quantitative ultrasound (QUS) at both heels. We hypothesized that football players have less contralateral variability in QUS measurements than that in normally active individuals due to the bilateral impact loading characteristics of football. Methods. Eighteen professional football players, aged 18-31 years, and 36 age-matched non-athletic controls participated in this study. Calcaneal QUS parameters [broadband ultrasound attenuation (BUA) and speed of sound (SOS)] were measured at both heels in all subjects using a gel coupled QUS device. Results. Football players had significantly higher BUA and SOS mean values (30.6% and 45.5% higher mean BUA and 3.38% and 3.87% higher mean SOS values, for the right and the left heels, respectively) than those in non-athletic controls (P=0.0001). Significant side differences were found in the mean values of BUA in the non-athletic subjects (P=0.001), but not in the footballers (P=0.538). The football players showed slightly higher BUA and SOS mean values on the left than those on the right side. While the number of football players who showed higher BUA values on either side was similarly distributed, significantly greater number of normally active males showed higher BUA values on the right side. Absolute and percentage side differences for BUA and the percentage of subjects who showed a bilateral BUA difference exceeding coefficient of variation %, expected from the repeated measurements of the same foot, in footballers were significantly less than those in the non-athletic subjects. Conclusion. The results of the present study show that high-impact loading of both calcanei in football is reflected by acoustic parameters of bone both in terms of overall enhanced bone properties and also in terms of the improvement of bone properties (as mainly reflected by BUA) on the non-dominant side as well.